Using graphene oxide based material for thermal sorption - Bui, Thi Le Thuy; Dao, Dinh Thuan; Pham, Dinh Thao (JST: Engineering And Technology For Sustainable Development, 2021)
In this work, some nanocomposite materials based on graphene oxide (GO) (Al2O3/GO, Fe3O4/GO, Fe3O4–Al2O3/GO) were prepared and characterized by X-ray and infrared spectra, SEM and EDX analysis. GO based materials were dispersed into salty water and the thermal absorption ability of mixtures was measured. Results showed that thermal sorption of composite materials was greater than that of single materials. Fe3O4–Al2O3/GO gives the highest thermal absorption efficiency (the temperature difference between the blank sample and the sample containing Fe3O4–Al2O3/GO with content of 0.5 mg/mL is 6 °C). The influence of the material content in salty water on the thermal sorption efficiency was investigated and a suitable concentration of 0.5 mg/mL was found. 98 % of Fe3O4–Al2O3/GO was recovered with the magnet because of its magnetic property and thermal absorption of recovered material are similar to that of the fresh material. The research results show the potential of using these nanocomposite materials to increase the efficiency of thermal sorption in the process of distilling salty water into fresh water.